An in vitro evaluation of the biological and osteogenic properties of magnesium-doped bioactive glasses for application in bone tissue engineering - Hohenbild, Frederike; Arango Ospina, Marcela; Schmitz, Sarah I.; Moghaddam, Arash; Boccaccini, Aldo R.; Westhauser, Fabian (International Journal of Molecular Sciences, 2021)
Magnesium (Mg2+ ) is known to play a crucial role in mineral and matrix metabolism of bone tissue and is thus increasingly considered in the field of bone tissue engineering. Bioactive glasses (BGs) offer the promising possibility of the incorporation and local delivery of therapeutically active ions as Mg2+ . In this study, two Mg2+-doped derivatives of the ICIE16-BG composition (49.46 SiO2, 36.27 CaO, 6.6 Na2 O, 1.07 P2 O5, 6.6 K2 O (mol%)), namely 6Mg-BG (49.46 SiO2, 30.27 CaO, 6.6 Na2 O, 1.07 P2 O5, 6.6 K2 O, 6.0 MgO (mol%) and 3Mg-BG (49.46 SiO2, 33.27 CaO, 6.6 Na2 O, 1.07 P2 O5, 6.6 K2 O, 3.0 MgO (mol%)) were examined. Their influence on viability, proliferation and osteogenic differentiation of human mesenchymal stromal cells (MSCs) was explored in comparison to the original ICIE16-BG. All BGs showed good biocompatibility. The Mg2+-doped BGs had a positive influence on MSC viability alongside with inhibiting effects on MSC proliferation. A strong induction of osteogenic differentiation markers was observed, with the Mg2+-doped BGs significantly outperforming the ICIE16-BG regarding the expression of genes encoding for protein members of the osseous extracellular matrix (ECM) at certain observation time points. However, an overall Mg2+-induced enhancement of the expression of genes encoding for ECM proteins could not be observed, possibly due to a too moderate Mg2+ release. By adaption of the Mg2+ release from BGs, an even stronger impact on the expression of genes encoding for ECM proteins might be achieved. Furthermore, other BG-types such as mesoporous BGs might provide a higher local presence of the therapeutically active ions and should therefore be considered for upcoming studies.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Human mesenchymal stromal cell; ICIE16 bioactive glass; Magnesium; Osteogenic differentiation; Therapeutically active ions